Kinetics of Homogeneous Reaction of Potassium Methoxide Based on K2CO3 Catalyst in Transesterification of RBDPO to Biodiesel - Salam, Yosirham Abdu; Komariah, Leily Nurul; Hadiah, Fitri; Arita, Susila (Science and Technology Indonesia, 2024)
Biodiesel production is generally catalyzed by potassium methylate or sodium methylate catalysts based on KOH and NaOH and these catalysts are still imported. The search for a cheap and effective catalyst continues to be carried out by researchers. One of the catalyst support materials currently in use involves impregnating K2CO3 with various substances, resulting in a heterogeneous catalyst. In this study, it was tried to use K2CO3 dissolved in methanol to produce a homogeneous potassium methylate catalyst. Potassium methylate-based homogeneous catalyst K2CO3-methanol is proven to have a very high function in the transesterification reaction of Refined Bleached Deodorized Palm Oil (RBDPO) into biodiesel, this is evidenced by the use of a catalyst percentage of 2% w and 30% w methanol to the weight of RBDPO resulting in an acid content in biodiesel of only 0.12% and a total glycerol of 0.124% in reaction time 3 hours, with the purity of the methyl ester in biodiesel reaching 98.80%. Meanwhile, for the calculation of homogeneous reaction kinetics, a reaction rate equation is produced where the order of the RBDPO transesterification reaction is order 2 (two) and the reaction rate constant is 0.0044.